Casebook in child behavior disorders - Kearney, Christopher A. (Belmont, CA : Wadsworth, 2006)
15 in-depth cases that help you explore the complexities of child behavioral disorders.
Includes bibliographic references and index.
Keywords: Child psychopathology -- Case studies; Child behavior disorders -- diagnosis; Child behavior disorders -- therapy; Child development